To question of threshold (maximum) situations in hydrologic-geomorphic watershed system - Kostrikov, S. V.; Beregniy, V. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
This paper represents some theoretical principles and applied software implementation of geomorphic threshold modeling. The paper discusses both the system approach in geomorphology and the geomorphic threshold concept as well as the following base definitions: “hydrologic-geomorphic watershed system”, “geomorphic threshold”, and “watershed sensitivity”. There have been suggested some mathematical tools for geomorphic threshold description. Two separate geomorphic threshold ratio models have been suggested. The approach given has been implemented for three watersheds in the upper part of Oskil-river basin with a GIS-model of this area. The threshold exceeding has been modeled in this way.